2015
DOI: 10.1002/chem.201406172
|View full text |Cite
|
Sign up to set email alerts
|

Columnar Liquid‐Crystalline Dinaphthoperylenetetracarboxdiimides

Abstract: Although the double Friedel-Crafts acylation of arenes with ethyl chloroglyoxylate is hindered by the strongly deactivating effect of the first-entering glyoxylic substituent, the double reaction is successful with the reactive arene perylene under long reaction times and with concomitant ester hydrolysis. The reaction is regiospecific, giving the 3,9-regioisomer exclusively. This perylenylenediglyoxylic acid is condensed first with o-bromophenylacetic acid and then with α-branched alkylamines to yield the tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Recently we have found that dissymmetrizing the swallow‐tail alkyl residues greatly improves the columnar mesogenic behavior of various polycyclic aromatic di‐ and tri‐imides, racemic 1‐hexyldecyl being particularly efficient in inducing large mesophase temperature ranges . As dissymmetric 1‐hexyldecyl differs only very moderately from symmetric 1‐heptyloctyl (as in 1 ) in combined alkyl chain lengths, we hoped that it would also induce a mesophase over large temperatures in PDI 3 .…”
Section: Methodsmentioning
confidence: 98%
“…Recently we have found that dissymmetrizing the swallow‐tail alkyl residues greatly improves the columnar mesogenic behavior of various polycyclic aromatic di‐ and tri‐imides, racemic 1‐hexyldecyl being particularly efficient in inducing large mesophase temperature ranges . As dissymmetric 1‐hexyldecyl differs only very moderately from symmetric 1‐heptyloctyl (as in 1 ) in combined alkyl chain lengths, we hoped that it would also induce a mesophase over large temperatures in PDI 3 .…”
Section: Methodsmentioning
confidence: 98%
“…Mesogenic materials with two such imide moieties are rare because two substituents are often not enough to induce liquid crystalline behavior, but the use of α‐branched (“swallow‐tailed”) alkylimide substituents RR′CHN(CO‐) 2 yields in some cases columnar mesophases, especially if the two branches R and R′ are not identical, yielding stereoisomeric mixtures with increased stabilization of the mesophase against crystallization 4. 5…”
Section: Introductionmentioning
confidence: 99%
“…Having recently found that swallow‐tailed dinaphtho[1,2‐b; 1,2‐k]perylene‐tetracarboxdiimides 1 , derived from centrosymmetric perylenylene‐3,9‐diglyoxylic acid 2 through a double Perkin condensation with 2‐bromophenylacetic acid 3 (Figure 1), form enantiotropic columnar mesophases,5 we aimed at preparing analogous dinaphtho[2,1‐a;2,1h]pyrene‐diimides 4 by a two‐fold Friedel–Crafts alkylation of pyrene with ethyl chloroglyoxylate ClCOCO 2 Et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Synthesis of dibenzopentacenodithiophene‐tetraester 9 and related dinaphthoperylene‐tetraester 3 , and structure of the derived diimides 7 and 4 together with complementary acceptor‐type perylene‐diimide 5 …”
Section: Figurementioning
confidence: 99%